Thoracoscopic Lung Segmentectomy Simulated by a Tailor-Made Virtual Lung: Computed Bronchography and Angiography - Akiba, Tadashi; Morikawa, Toshiaki; Ohki, Takao (The Thoracic and Cardiovascular Surgeon, 2013)
We describe the benefits of simulating an anatomical lung segmentectomy using multidetector computed tomography bronchography and angiography (tailor-made virtual lung). Preoperative determination of the anatomical intersegmental plane is possible by visualizing the segmental bronchi and pulmonary vein branches. This advanced technique could be useful during thoracoscopic anatomical segmentectomy for lung cancer.
Keywords: thoracoscopy/VATS; lung cancer treatment (surgery medical); computed tomography; CT scan; pulmonary arteries/veins